Dearomative [4 + 3] cycloaddition of furans with vinyl-N-triftosylhydrazones by silver catalysis: stereoselective access to oxa-bridged seven-membered bicycles. Issue 9 (24th March 2022) - Liu, Zhaohong; Yang, Yong; Jiang, Xinyu; Song, Qingmin; Zanoni, Giuseppe; Liu, Shaopeng; Bi, Xihe
Abstract : A practical dearomative [4 + 3] cycloaddition of furans with vinylcarbenes to access oxa-bridged seven-membered carbocycles, with complete and predictable stereoselectivity, is achieved by merging silver catalysis and vinyl- N -triftosylhydrazones. Abstract : The first example of dearomative [4 + 3] cycloaddition between furans and vinyl- N -sulfonylhydrazones as vinylcarbene precursors is reported. The merger of silver catalysis and easily decomposable vinyl- N -triftosylhydrazones enabled the efficient synthesis of a variety of skeletally and functionally diverse oxa-bridged seven-membered bicyclic compounds with complete and predictable stereoselectivity. The combination of experimental studies and DFT calculations disclosed that the silver-catalyzed reaction proceeds via a concerted [4 + 3] cycloaddition mechanism, rather than the generally accepted cyclopropanation/Cope rearrangement pathway by rhodium catalysis.